A comparative evaluation of crumb rubber and devulcanized rubber modified binders. (3rd June 2017) - Ghasemirad, Amirhossein; Asgharzadeh, Seyed Mohammad; Tabatabaee, Nader
ABSTRACT: One of the most prominent uses of ground tire rubber (GTR) is in rubber-modified asphalt industry. Besides improving performance properties of binders, GTR induces some drawbacks like weak storage stability and inferior low temperature (LT) performance. This study sought to rectify these shortcomings through using devulcanized rubber (DVR) in place of common GTR. Binder performance grading, multiple stress creep and recovery, and storage stability tests were conducted. More resistance against traffic loads at high temperatures was observed as DVR's advantages over GTR, while its weaker LT characteristics and lower storage stability can prevent it from being a viable alternative.